2014
DOI: 10.1161/str.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

Palliative and End-of-Life Care in Stroke

Abstract: Background and Purpose-The purpose of this statement is to delineate basic expectations regarding primary palliative care competencies and skills to be considered, learned, and practiced by providers and healthcare services across hospitals and community settings when caring for patients and families with stroke. Methods-Members of the writing group were appointed by the American Heart Association Stroke Council's Scientific Statement Oversight Committee and the American Heart Association's Manuscript Oversigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
131
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 243 publications
(135 citation statements)
references
References 287 publications
(286 reference statements)
0
131
0
4
Order By: Relevance
“…Similar to findings from other smaller studies, 6 this suggests a mismatch between practice reality and stroke guidelines, which recommend time-limited trials of nasogastric feeding for a period of ≤2 to 3 weeks prior to placing a surgical feeding tube. 7 We found that age was the greatest determinant of early PEG tube placement. In fact, the oldest PEG tube recipients (≥85 years) had 1.7× the adjusted odds of receiving an early PEG compared with the youngest (18-54 years), and there were no differences in discharge disposition for those receiving their PEG early versus later in this subset of older patients.…”
Section: Discussionmentioning
confidence: 72%
“…Similar to findings from other smaller studies, 6 this suggests a mismatch between practice reality and stroke guidelines, which recommend time-limited trials of nasogastric feeding for a period of ≤2 to 3 weeks prior to placing a surgical feeding tube. 7 We found that age was the greatest determinant of early PEG tube placement. In fact, the oldest PEG tube recipients (≥85 years) had 1.7× the adjusted odds of receiving an early PEG compared with the youngest (18-54 years), and there were no differences in discharge disposition for those receiving their PEG early versus later in this subset of older patients.…”
Section: Discussionmentioning
confidence: 72%
“…It remains unclear however, whether the higher mortality rate and more frequent use of comfort measure in whites are reflective of patient/family preferences, treatment futility, or failure to provide appropriate care to patients who still have the possibility of favorable outcomes. 35 Therefore, if mortality is to be one of the metrics to quantify ICH care quality, great caution should be undertaken in interpreting these results.…”
Section: November 2014mentioning
confidence: 99%
“…The purposes of this policy statement are to provide background on the importance of palliative care as it pertains to patients with CVD and stroke and their families and to make recommendations for policy decisions (Appendix 1). Two recent scientific statements by the AHA/ASA, "Palliative and End-of-Life Care in Stroke" 1 and "Decision Making in Advanced Heart Failure," 2 informed the writing of this policy statement.…”
Section: Introductionmentioning
confidence: 99%